1997
DOI: 10.1074/jbc.272.7.4295
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Heme Oxygenase-1 Expression in Vascular Smooth Muscle Cells

Abstract: Endotoxic shock is a life-threatening consequence of severe Gram-negative infection characterized by vascular smooth muscle cell relaxation and severe hypotension. The production of nitric oxide (NO), through the inducible NO synthase pathway, has been implicated as a major contributor in this process. We now demonstrate that heme oxygenase (HO), an enzyme that generates carbon monoxide (CO) in the course of heme metabolism, may also be involved in the hemodynamic compromise of endotoxic shock. Inducible HO (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 35 publications
6
153
2
Order By: Relevance
“…This include the ability of CO to promote vasodilatation (36) by the induction of smooth muscle cell relaxation (26,37). Vasodilatation may contribute to prevent vascular thrombosis, which would be important in suppressing graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…This include the ability of CO to promote vasodilatation (36) by the induction of smooth muscle cell relaxation (26,37). Vasodilatation may contribute to prevent vascular thrombosis, which would be important in suppressing graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities and diversities of the NO/NOS and CO/ HO systems were well established in numerous studies (11,14), but the interactions between these systems have not yet been elucidated. The interactive behavior of the two systems has been examined in monocytic cells (7), vascular endothelial cells (4), and vascular smooth muscle cells (22), and accumulating evidence from these studies has shown that the NO/NOS system induces the CO/HO system, while the CO/HO system reciprocally regulates the NO/NOS system. The relationship between the two systems in whole organs, on the other hand, has not been well studied, and it is unknown whether the two systems interact in the same manner in all organs or whether the two systems interact in an organ-specific manner.…”
Section: Real-time Reverse Transcriptase-polymerase Chain Reaction (Rmentioning
confidence: 99%
“…The common conception that these enzymes are merely components of a catabolic pathway that facilitates the elimination of toxic products from the organism has been disputed by strong evidence demonstrating that endogenously generated CO and bilirubin act as crucial effector molecules in the mitigation of vascular and cellular dysfunction (4 -12). Disparate conditions and a number of pathological states including hypoxia, endotoxic shock, atherosclerosis, and inflammation have been found to promote overexpression of the HO-1 gene and increased heme oxygenase activity (13)(14)(15)(16)(17)(18). Although the molecular mechanism(s) leading to HO-1 induction by these and other conditions remains to be fully elucidated, a common denominator that characterizes the prompt stimulation of HO-1 under most circumstances is the transient decrease in cellular glutathione levels and a drastic change in the redox status of the intracellular milieu (15, 19 -21).…”
mentioning
confidence: 99%